A Comprehensive Biomechanical and Clinical Analysis of a Youth Ambidextrous Baseball Pitcher: A Case Report - Sarah L. Woelfel; Dimitri D. Haan; Cameron B. Jensen; Katie T. Martens; Adam B. Rosen; Samuel J. Wilkins; Brian A. Knarr (International Journal of Sports Physical Therapy, 2025)
# Background